(untitled) (Academicia Globe: Inderscience Research, 2024)
This study investigated the relationship between hospitality work environment and labour turnover Intent in small-sized hotels in Diobu, Port Harcourt. The cross sectional survey design was adopted for the study whereby data were obtained through the questionnaire method from 122 employees purposively drawn from 10 small-sized hotels operating in the Diobu area of Port Harcourt. Both descriptive and inferential statistical tools were deployed for data analysis. Simple percentage, mean score and standard deviations were utilized for descriptive analysis whereas the Pearson Product Moment Correlation (PPMC) coefficient technique was adopted for the test of hypotheses, aided by the Statistical Package for Social Sciences (SPSS), version 21, tested at 5% level of significance. The findings revealed that the physical work environment factors (workplace safety and atmospheric conditions) were favourably perceived by employees, however, the psychological components (job security and pay) were not well perceived by the employees, which could not support employee retention. Based on the findings, it was concluded that the dimensions of hospitality work environment (workplace safety/hygiene, atmospheric conditions, job security and pay) correlated with labour turnover intent. Therefore, it was recommended that the hotels should continue to maintain workplace safety/hygiene standard and improve on employee incentive system for improved productivity, employee commitment and retention.